Sandwich teaching improved students' critical thinking, self-learning ability, and course experience in the Community Nursing Course: A quasi-experimental study - Cai, Xiaoyan; Peng, Mingmei; Qin, Jieying; Zhou, Kebing; Li, Zhiying; Yang, Shuai; Yan, Fengxia (Frontiers in Psychology, 2022)
The youngest generation of students prefer a more active learning style. Sandwich teaching may suit their learning style by alternating between active individual learning and passive collective learning. Sandwich teaching has been rarely applied to the Community Nursing Course for nursing students, and its teaching effects on this course remain unclear. This study applied Sandwich teaching to the Community Nursing Course for Chinese nursing undergraduates, and investigated its effects on students’ critical thinking, self-learning ability, course experience, and academic performance. This is a quasi-experimental study with 72 Chinese nursing undergraduates. Students of Grade 2018 receiving traditional teaching were enrolled into the control group (n=36), and students of Grade 2019 were recruited into the experimental group (n=36) to receive Sandwich teaching. Both group received the twelve-week ninety-minute Community Nursing Course. Our main outcome variable, including students' critical thinking and self-learning ability, and course experience, were assessed by specific questionnaire. The paired t-tests were applied to compare the differences of the same group in the pre-test and the post-test, and the independent-sample t-tests were used to compare the differences between two groups. We observed that nursing students' critical thinking ability and self-learning ability were significantly improved after receiving Sandwich teaching. Students' course experience of Sandwich teaching was significantly better than that of traditional teaching. The final exam score in the the experimental group was not significantly higher than that in the control group. These results suggest that Sandwich teaching in Community Nursing Course improved Chinese nursing undergraduates’ critical thinking, self-learning ability, and course experience, but failed in improving academic performance.